2021
DOI: 10.1111/bjet.13063
|View full text |Cite
|
Sign up to set email alerts
|

Using assistive technology with SRSD to support students on the autism spectrum with persuasive writing

Abstract: Children on the autism spectrum (AS) often struggle with writing tasks at school. They commonly experience difficulty with two key aspects of writing: the skills required for handwriting (fine motor and perceptual) and the conceptual and language skills required for written composition. Specialist intervention to assist with written expression is, therefore, often needed for students on the AS to succeed academically. This research evaluated the impact of using self‐regulated strategy development (SRSD) in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Graham and Perin (2007), in their meta-analysis study on adolescents, determined that this model is very effective in developing the writing skills of different target audiences (students with learning disability, child with typical development etc.). Similarly, in studies supported by SRSD and SRSD applied in the dates after this meta-analysis study, it has been revealed that this model is also effective on different target groups (e.g., Festas et al 2015;Ozdowska, Wyeth, Carrington, & Ashburner 2021;Palermo and Thomson 2018;Rosário et al 2019;Traga Philippakos, & MacArthur). However, the SRSD model is a strategy teaching model (Garcia-Sanchez & Raquel Fidalgo-Redondo, 2006;Uyar, 2015).…”
Section: Introductionmentioning
confidence: 78%
“…Graham and Perin (2007), in their meta-analysis study on adolescents, determined that this model is very effective in developing the writing skills of different target audiences (students with learning disability, child with typical development etc.). Similarly, in studies supported by SRSD and SRSD applied in the dates after this meta-analysis study, it has been revealed that this model is also effective on different target groups (e.g., Festas et al 2015;Ozdowska, Wyeth, Carrington, & Ashburner 2021;Palermo and Thomson 2018;Rosário et al 2019;Traga Philippakos, & MacArthur). However, the SRSD model is a strategy teaching model (Garcia-Sanchez & Raquel Fidalgo-Redondo, 2006;Uyar, 2015).…”
Section: Introductionmentioning
confidence: 78%
“…This was obtained by testing fine motor skills whereby learners WHO were finding out remotely were tasked to repeat shapes and drawings of the person and rate their mastery of fine motor skills. a special study by conducted in Australia by Ozdowska, Wyeth, Carrington, and Ashburner (2021) exploitation helpful technology with SRSD to support students on the syndrome spectrum with persuasive writing with eight school students on the syndrome Spectrum between the ages of nine and twelve participated during this single-subject study shows that in several cases the standard and/or length of written compositions and feelings of self-efficacy towards persuasive writing of scholars on the AS improved after they received physical and/or abstract writing supports. In light-weight of those results, one could infer that fine motor skills are necessary for children's development because it helps them to jot down quality papers.…”
Section: Discussionmentioning
confidence: 98%
“…The use of these tools for SWDs is federally mandated under the Individuals with Disabilities Act (IDEA; Rowland, 2020) and students without disabilities may also benefit from them (Dawson et al, 2019). Numerous studies support the use of these technologies for students with and without disabilities (i.e., Jozwik et al, 2020;Ozdowska et al, 2018;Ozdowska et al, 2021;Park et al, 2017). Specifically, students with physical disabilities, learning disabilities, and those that struggle with spelling and vocabulary have been shown to benefit from the use of word prediction (Evmenova & Regan, 2019) and high schoolers with SLD improved their writing quality when using speech-to-text rather than handwriting (Evmenova & Regan, 2019).…”
Section: How To Choose the Correct Toolmentioning
confidence: 99%